The effect of product quality, trust, and satisfaction on customer loyalty at PT X - Raudah, Raudah; Wasiman, Wasiman (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the influence of product quality, trust, and satisfaction on customer loyalty at PT X, an automotive service company. Using a quantitative approach with 100 respondents and data analyzed through SPSS 25, the results reveal that all three independent variables, product quality, trust, and satisfaction, have positive and significant effects on customer loyalty, both partially and simultaneously. Product quality emerged as the most dominant factor influencing loyalty, while trust and satisfaction contributed to strengthening long-term customer relationships. The findings imply that improving product quality, maintaining customer trust, and enhancing satisfaction are essential strategies for developing sustainable customer loyalty. This research also reinforces consumer behavior theories asserting that loyalty is built through the combined effect of perceived quality, trust, and satisfaction, offering both theoretical and managerial insights for similar industries